2014
DOI: 10.3389/fnmol.2014.00016
|View full text |Cite
|
Sign up to set email alerts
|

Protein phosphatase 2A dysfunction in Alzheimer’s disease

Abstract: Protein phosphatase 2A (PP2A) is a large family of enzymes that account for the majority of brain Ser/Thr phosphatase activity. While PP2A enzymes collectively modulate most cellular processes, sophisticated regulatory mechanisms are ultimately responsible for ensuring isoform-specific substrate specificity. Of particular interest to the Alzheimer’s disease (AD) field, alterations in PP2A regulators and PP2A catalytic activity, subunit expression, methylation and/or phosphorylation, have been reported in AD-af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
214
0
14

Year Published

2016
2016
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 264 publications
(238 citation statements)
references
References 110 publications
(142 reference statements)
10
214
0
14
Order By: Relevance
“…The present findings point to parallels in the dysregulation of PP2A, and in particular its methylation state, between α ‐synucleinopathies and Alzheimer's disease 34. Decreased phosphatase activity toward abnormally phosphorylated tau had been recognized in AD brains 59.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…The present findings point to parallels in the dysregulation of PP2A, and in particular its methylation state, between α ‐synucleinopathies and Alzheimer's disease 34. Decreased phosphatase activity toward abnormally phosphorylated tau had been recognized in AD brains 59.…”
Section: Discussionsupporting
confidence: 58%
“…In assessing the regulatory parameters that might control PP2A carboxyl methylation in the CNS, there has been a focus on factors that underlie methylation metabolism such as levels of the methyl donor, S‐adenosylmethionine (SAM), the competitive inhibitor, S‐adenosyl homocysteine (SAH), or the methylation cycle intermediate homocysteine. Accordingly, there is considerable evidence that SAM and SAH levels play a substantial role in regulating PP2A 30, 31, 32, 33, 34. Conditions of methylation and one carbon stress have been shown to cause DNA hypomethylation at loci that appear to contribute to the pathogenesis of PD 35, 36, 37.…”
Section: Discussionmentioning
confidence: 99%
“…Analyses conducted on postmortem AD brains have found reduced PP2A expression and activity, and studies conducted in animal models have found that inhibiting PP2A produces AD-like tau pathology and cognitive impairment (1)(2)(3). One of the ways in which PP2A may affect AD is through its role as the principal tau phosphatase (4)(5)(6)(7).…”
mentioning
confidence: 99%
“…PP2A also interacts with a number of kinases implicated in AD including glycogen synthase kinase 3β (GSK3β), cyclindependent kinase 5 (CDK5), and ERK and JNK as well as amyloid precursor protein and the NMDA and metabotropic glutamate receptors (reviewed in ref. 2).…”
mentioning
confidence: 99%
“…All these modifications may affect the interaction with more than 70 predicted tau binding partners [11], including the tyrosine kinase fyn, the membrane-associated protein annexin A2, and its effector protein phosphatase PP2A [66][67][68]. Despite this plethora of regulatory systems and interactions, knockout mice lacking a functional tau gene do not display severe defects in brain function or development [69], which suggests the presence of redundant and compensatory mechanims in vertebrates.…”
Section: Posttranslational Modifications Influencing Tau Toxicitymentioning
confidence: 99%